The Ancient Assyrians - Healy, Mark. (Oxford, UK ; New York, NY)
320 sayfa
Keywords: “Drawing on 30 years of scholarship, this is a unique, richly illustrated history of the Ancient Assyrian Army and Empire. For the greater part of the period from the end of the 10th century to the 7th century BC, the Ancient Near East was dominated by the dynamic military power of Assyria. This book examines the empire that is now acknowledged as the first `world' empire, and thus progenitor of all others. Fully illustrated in colour throughout, with photographs of artefacts, drawings and maps, it focuses on the Assyrian Army, the instrument that secured such immense conquests, now regarded by historians as being the most effective of pre-classical times. It was not only responsible for the creation of history's first independent cavalry arm, but also for the development of siege weapons later used by both Greece and Rome. There is a great deal of visual evidence showing how this army evolved over three centuries. During the rediscovery and excavation of the Assyrian civilisation in the mid-19th century, many wall reliefs and artefacts were recovered, and the enormous amount of research carried out by Assyriologists since that time has revealed the immense impact of the Assyrian Empire on history. Such has been the scale of archaeological discovery in more recent years that it is now possible to give the actual names of chariot/cavalry unit commanders. Drawing on this rich scholarship, and utilising the fantastic collections of museums around the world, Mark Healy presents a unique new history of this fascinating army and empire.” --